STRATEGI HARMONISASI REGULASI HUBUNGAN PUSAT DAN DAERAH - Abd Rais Asmar (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2018)
Harmonization of regulation between center government and regional government at harmonious how in relation center government and regional government which consist of relation of power (distribution of governmental affairs), monetary, and controlling. Third of this relation component can walk harmonious if regulasi arranging it harmonious also. Law about Local Government can be made as mains law to start to repair of relation center government and regional government in regulation.